Functional possibilities of the system's substitute models (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2009)
On the basis of the use of frequency-quantum ability of the systems of substituting for the first type possibilities of transmission of signals are analysed with a limit on the greatest frequency and level of distortions.